HYDRAULIC EFFICIENCY OF THE DISCONTINUOUS GULLIES - Ionita I. (My University, 2003)
Most discontinuous gullies overlying the almost tabular sedimentary strata of the Moldavian Plateau, Eastern Romania exhibit gullying by gully head advance and aggradation of the gully basin floor. According to Heede [Z. Geomorphol. N. F. 18 (1974) 260] the shape factor of the gullies, relating maximum to minimum depth, expresses both channel shape and hydraulic efficiency of channels.Based on a geomorphic approach, this paper shows that a better understanding of gully hydraulic efficiency may be assessed by another shape factor obtained by relating present to filled gully cross-section. A value of 1.0 for this shape factor, Sp/Sf, represents the threshold of hydraulic efficiency. Strong relationships were established between the shape factor and gully length. In addition, an appropriate substitute expressed as the ratio of gully bottom width (Wb) to gully top width (Wt) was found, which is easy to apply and very fast to determine in the field.
Keywords: DISCONTINUOUS GULLIES; GULLYING; AGGRADATION; SHAPE FACTOR; HYDRAULIC EFFICIENCY